Development of multiple plug-in electric vehicle mobile charging station using bidirectional converter - A. Dominic Savio; Vimala Juliet A. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Electric vehicle (EV) charging station powered by the scattered energy sources with DC Nanogrid (NG) provides an option for uninterrupted charging. The NG powered by the renewable energy sources (RES) of photovoltaic (PV) and wind energy. When the excess power produced by the renewable energy stored in the local energy storage unit (ESU) utilized during shortage power from the renewable sources. During the overloading of NG and demand of energy in ESU; the mobile charging station (MCS) provides an uninterrupted charging. The MCS provides an option for battery swapping and vehicle to grid feasibility. The MCS required to monitor the state of charge (SOC) and state of health (SOH) of the battery. Monitoring of SOC and SOH related to the various battery parameters like voltage, current and temperature. A laboratory prototype is developed and tested the practical possibility of EV to NG and Internet of things (IoT) based monitoring of battery parameters.